GeB flat fibre TL dosimeters for in-vivo measurements in radiosurgery - Alyahyawi, A.; Dimitriadis, A.; Nisbet, Andrew; Bradley, D.A. * (Elsevier, 2021)
Noting an increase in demand for procedures involving clinical radiosurgery we seek to develop a high spatial resolution thermoluminescence dosimeter (TLD) to allow conduct of in vivo dose verification measurements. An associated need is for a dynamic dose range exceeding that of the well-established LiF (Mg,Ti) phosphor TLD-100, with in particular the latter being limited in performance at the elevated doses seen in radiotherapy. The work investigates the performance of a novel GeB co-doped Flat Fibre (GeB-FF) fabricated using the modified chemical vapour deposition (MCVD) process, the hollow capillary optical fibres (COF) produced from this being collapsed down into flat fibres (FF) to create strain-related defects. This process has already been demonstrated to increase the low dose sensitivity of optical fibres, notably at diagnostic x-ray potentials, with Minimum Detectable Dose (MDD) values of down to 0.1 μGy. The intent of present work, conducted as a component of a safety audit, part of the hospital periodic radiation protection quality assurance program, has been to examine and compare the performance of the two forms of TL dosimeter, GeB-FF and TLD-100, measuring scattered radiation resulting from cranial cavity radiosurgery procedures. The dosimeters were placed on the neck, chest and pelvis of 20 patients. Using both types of dosimeter, raw dose values at each site show general accord (±3 mGy at 1 σ), covering mean doses ranging from some 10 mGy to less than 1 mGy, representing doses of <1% to < 0.1% of prescribed dose at the treatment site. GeB-FF results uncorrected for energy response show absorbed doses greater than that using TLD-100, by factors of some 1.4, 1.2 and 1.5 for the pelvis, chest and neck respectively; energy corrections have been shown elsewhere to provide for much closer agreement.